2015
DOI: 10.1111/asj.12479
|View full text |Cite
|
Sign up to set email alerts
|

Development of a simple IgE‐independent anaphylactic model using buckwheat antigen and B‐type CpG oligodeoxynucleotide from Streptococcus thermophilus

Abstract: We developed a severe anaphylactic model in mice using buckwheat antigen and B-type CpG-oligodeoxynucleotides (CpG-ODNs) from Streptococcus thermophilus genome. In typical systemic anaphylaxis models, animals are challenged with large quantity of antigens via an intravenous (i.v.) route. Here, we showed a simple anaphylactic shock after challenge via intraperitoneal (i.p.) route. The i.p. method is simpler than i.v. administration and has a lower risk for failure. To generate this anaphylactic model, 5-week-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…injection with iSN34 + CpG-B. In previous work, we demonstrated that CpG-B is involved in activating the innate immune response and induces splenomegaly [ 29 , 46 ]. Indeed, splenomegaly has been considered an important complication of acute and chronic disease for more than 100 years [ 47 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…injection with iSN34 + CpG-B. In previous work, we demonstrated that CpG-B is involved in activating the innate immune response and induces splenomegaly [ 29 , 46 ]. Indeed, splenomegaly has been considered an important complication of acute and chronic disease for more than 100 years [ 47 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…PS-ODNs were reconstituted in phosphate-buffered saline (PBS) and passed through a 0.22-µm pore microfilter (Nihon Millipore K.K., Tokyo, Japan). ODN sequences are shown in Table 1 : CpG-A 1585 ( 48 ), CpG-B 1826 ( 49 ), CpG-C 2395 ( 50 ), Ctr 1612 ( 51 ), non-CpG-A 1585 , and iODN H154 ( 13 ). LPS from Escherichia coli 0127:B8 was purchased from Sigma-Aldrich (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Both the activation of T-helper-2 (Th2) cell immune responses and the immune regulation of regulatory T cells (Tregs) have been implicated in the pathogenesis of allergic reactions (3)(4)(5). An allergy is an excessive immune response to a specific environmental antigen that normally is tolerated by the general population; the term also has become synonymous with hypersensitivity (6). Th2 cells are thought to play a key role in the onset of allergic reactions, given that this class of cells produces the pro-inflammatory cytokines interleukin (IL)-4, IL-5, and IL-13, and induces the differentiation of B cells into plasma cells.…”
Section: Introductionmentioning
confidence: 99%